Nasal Septal Perforation Repair with an Inferior Turbinate Flap and Acellular Dermal Matrix - Mirzai, Saeid; Lee, Andrew H.; Chi, John J. (The Surgery Journal, 2021)
Nasal septal perforation is an uncommon disorder that can cause disturbance of nasal physiology. The perforations can vary widely in size, location, and symptomatology. Many different closure techniques have been described in the literature; however, no gold standard has been recognized. The choice of surgical technique usually depends on the characteristics of the perforation and surgeon experience. Due to the goal of perforation repair being restoration of normal nasal physiology, techniques with the best outcomes have been those resurfacing the septum with nasal respiratory mucosa. Here we present our novel surgical method for large (> 2 cm) septal perforation closure using a modification of the inferior turbinate flap repair using a polydioxanone plate and the acellular dermal matrix allograft (Alloderm, Allergan Inc.).
Keywords: nasal septal perforation; inferior turbinate flap; septal perforation repair; polydioxanone plate; acellular dermal matrix allograft